Didactive And Review Of Axiology Theorem Of Da'wah Science Development Of Islamic Society In Supporting Social Workers - Mubasit (CV. Inara, 2021)
The da'wah communication strategy is the basic policy of da'wah organizations which are options and alternatives that are directly related tothe achievement of da'wah goals, namely guiding relationships, organizing communication, developing and improving mad'u action patterns so that they are in accordance with Islamic teachings after considering internal conditions and external conditions. , then the main problem is: